Back Cover: Synthesis and Characterisation of Reduced Graphene Oxide/Bismuth Composite for Electrodes in Electrochemical Energy Storage Devices (ChemSusChem 2/2017). Issue 2 (20th January 2017) - Wang, Jiabin; Zhang, Han; Hunt, Michael R. C.; Charles, Alasdair; Tang, Jie; Bretcanu, Oana; Walker, David; Hassan, Khalil T.; Sun, Yige; Šiller, Lidija
Abstract : The Back Cover picture shows the structure of a reduced graphene oxide (rGO)/Bi composite material synthesized through a simple and scalable procedure. The material shows both supercapacitor and battery behavior (supercapattery behavior) and achieves a specific capacity value close to its theoretical value while atmospheric oxidation of metallic bismuth is inhibited by the reduced graphene oxide. More details can be found in the Full Paper by Wang et al. onpage 363 in Issue 2, 2017 (DOI:10.1002/cssc.201601553 ).